2017
DOI: 10.3390/toxins9080236
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Toxins for Cancer Therapy

Abstract: Several pathogenic bacteria secrete toxins to inhibit the immune system of the infected organism. Frequently, they catalyze a covalent modification of specific proteins. Thereby, they block production and/or secretion of antibodies or cytokines. Moreover, they disable migration of macrophages and disturb the barrier function of epithelia. In most cases, these toxins are extremely effective enzymes with high specificity towards their cellular substrates, which are often central signaling molecules. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…For example, it has been discovered that the selective activation of RhoA/B/C by Yersinia cytotoxic necrotizing factor (CNFy) can stimulate the apoptotic pathway in specific tumor cells in which CNF1 has no effect [ 48 ]. Another alternative could be represented by immunotoxins, in order to precisely select the target cells through the specificity of an antibody [ 13 , 68 ]. Therefore, the use of more selective toxins might be a feasible new avenue for tumor treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been discovered that the selective activation of RhoA/B/C by Yersinia cytotoxic necrotizing factor (CNFy) can stimulate the apoptotic pathway in specific tumor cells in which CNF1 has no effect [ 48 ]. Another alternative could be represented by immunotoxins, in order to precisely select the target cells through the specificity of an antibody [ 13 , 68 ]. Therefore, the use of more selective toxins might be a feasible new avenue for tumor treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, toxins represent a promising tool for GBM therapy because of their features in terms of specificity and biological action. In particular, (i) toxins are extremely potent and not subjected to mechanisms of drug resistance; (ii) the active core of the toxins can be isolated and cloned becoming small in molecular size, and thus more efficient to penetrate into solid tumors; (iii) toxins can be combined by recombinant DNA technology with selective carriers or antibodies (Abs) against surface receptors, thus allowing specific entry of the catalytic toxin domain into selected tumor cell types [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many bacterial toxins have been extensively studied for their promising clinical applications [47][48][49][50][51]. A previous study has shown that human gingival squamous carcinoma cell line Ca9-22 transfected with Actinobacillus actinomycetemcomitans-CdtB-expressing plasmid manifested G2 phase arrest and cell growth inhibition [52].…”
Section: Discussionmentioning
confidence: 99%
“…The IL-2 moiety allows for selective targeting of IL-2R bearing cells. Upon IL-2 and IL-2R binding, the fusion protein is internalized and transported to the cell cytosol where the catalytic domain inhibits protein synthesis resulting in downstream alterations that ultimately lead to apoptosis (Zahaf and Schmidt, 2017). DD has been approved for treatment of cutaneous T cell lymphoma and subsequent human studies.…”
Section: T Cell Therapiesmentioning
confidence: 99%